Edukasi Menjaga Kesehatan Mental melalui Pendekatan Komunikasi Antar Pribadi pada Siswa SMA PGRI 3 Jakarta - Ashfahani, Shulhuly; Nurhuda, M. Miftahul; Fauziah, Azizah Sholy; Saputra, Ardhi (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The level of awareness Indonesian society regarding mental health, especially among teenagers, is still minimal, therefore lecturer and students from Faculty of Communication Sciences, University of Indonesia Maju provide education regarding how to maintain mental health for students at SMA PGRI 3 Jakarta. Mental health is a form of true balance of mental functions and the creation of adjustment between humans, themselves and their surrounding environtment. The method used in this community service is the lecture and discussion method. The results of community service activities for educational participants regarding interpersonal communication approaches in maintaining the mental health of SMA PGRI 3 Jakarta students begin to open up and increase their knowledge regarding maintaining mental health. These result were obtained from the evaluation form filled in by participants and observations during the discussion process.